IDENTIFIKASI CEMARAN BAKTERI (Escherichia coli) TERHADAP IKAN KEMBUNG DAN IKAN DENCIS YANG DIJUAL DI PASAR TRADISIONAL DELI TUA - Firdaus Fahdi; Dwi Pratiwi; Helviani Sari (Jurnal Penelitian Farmasi & Herbal, 2020)
Introduction : Fish is a food that is easily damaged by enzymes or microorganism’s biological decay, thus requiring special handling. The process of spoilage of fish can be caused mainly by the activity of enzymes found in the body. This study aims to find out whether there are contaminants of Escherichia coli on mackerel (Rastrelliger sp) and dencis fish (Decapterus russelli) which are sold at the Deli Tua traditional market. Method : This type of research is true experimental with a Post Test Only Control Group Design. Sample was collected from the traditional market in Deli Tua with purposive sampling. Result : from the observation of the number of bacterial colonies on the PCA media with mackerel and dencis fish samples in accordance with SNI because it exceeds 5,0X105 CFU/g. Conclusion : From the results of the study note that there is the contamination of Escherichia coli bacteria in mackerel (Rastrelliger sp) and Dencis fish (Decapterus russelli) which are sold in the Deli Tua traditional market.